TRANSLATION PROCEDURES USED IN TRANSLATING COMPUTER TERMS FROM ENGLISH INTO BAHASA INDONESIA - Ozy Hadithya (Vivid: Journal of Language and Literature, 2014)
This research is aimed to identify the computer terms and procedures used by the translator in translating the book Wireless Networking in the Developing World 2nd edition from English into Indonesian. In analyzing the data, the writer applies the theory proposed by Vinay and Dalbernet (in Hatim and Munday 2004:148). This theory divides translation method into two parts: (1) literal translation, and (2) oblique translation, with the seven procedures: (a) borrowing, (b) Calque, (c) literal translation, (d) transposition, (e) modulation, (f) equivalence and (g) adaptation. Having analyzed 31 data, the writer found that borrowing is the most dominant procedure used by the translator in translating the computer terms into the target language. Besides that, the translator also uses borrowing combined with transposition, calque and literal translation procedures in translating the computer terms.Keywords: translation, translation procedures, computer term